Dynamics of the range and population of the European Mink (Mustela lutreola L., 1761) in Ukraine - Volokh, Anatolii; Волох, Анатолій Михайлович; Волох, Анатолий Михайлович; Rozhenko, N. (My University, 2011)
In the early 20th century the European mink range covered the basins of the Dniester, Dnieper, Danube, Siverskyi Donets, Pivdennyi Buh and some steppe rivers, flowing into the Azov Sea. In the mid 20th century there occurred a sharp reduction in numbers of the European mink in Ukraine caused by intensive man-made transformation of wetlands. In the forest zone especially heavy negative impact was caused by intensive reclamation of bogs and tree felling, and in the forest-steppe and steppe zones by building of dams of hydropower stations and intensification of agriculture in river floodplains.
Keywords: European Mink; range; biotopes; dynamics; trapping; Ukraine; population; Red Data Book of Ukraine